From the British museum to the longhouse: reclaiming the Pua Kumbu and revitalizing Iban cultural identity - Gregory Kiyai @ Keai, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Pua Kumbu is a type of woven cloth and a cultural object that has been a source of pride for the Iban people for generations. It holds great significance in Iban culture, to the point that Iban women are expected to master the craft at the highest level in order to place themselves in the highest social hierarchy within the longhouse community. However, this weaving art, rich in taboos, extraordinary stories about Iban gods and deities, and the Iban people's excellence in producing it through the environment, has become an object that was 'smuggled, stolen, and seized' by colonial powers and foreign researchers since the era of James Brooke in Sarawak and after the end of World War II. This powerful cultural object of the Iban people was handed over to The British Museum's collection and has never been returned to its place of origin. Therefore, this study discusses a selected collection of Pua textiles, based on its motifs, which are considered ancient motive and no longer produced in Iban weaving art in Sarawak after the cultural transformation of the indigenous people, especially following the formation and inclusion in the Federation of Malaysia in 1963.